2023
DOI: 10.3390/agronomy13061436
|View full text |Cite
|
Sign up to set email alerts
|

Bioponics—An Organic Closed-Loop Soilless Cultivation System: Yields and Characteristics Compared to Hydroponics and Soil Cultivation

Florentina Gartmann,
Julian Hügly,
Nikita Krähenbühl
et al.

Abstract: Sustainable food production has become increasingly important. Soilless cultivation systems offer several advantages, such as water and nutrient use efficiency, and can be implemented where traditional agriculture is impossible. Bioponic systems use locally or regionally available nutrient sources from organic waste streams (either fluid or solid) and can thus contribute to closing nutrient cycles locally. Bioponics harnesses the metabolic processes of microorganisms which release nutrients from organic matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
0
5
1
Order By: Relevance
“…The yield of lettuce grown in bioponic solution was only one fifth (21%) of the lettuce yield when grown in the Hoagland solution. This was lower than most other published results for yields of bioponically grown lettuce, relative to mineral nutrient solution grown lettuce as reported by Gartman et al [22], Williams and Nelsons [52], Liedl [10], and Atkins and Nichols [55], who obtained 72%, 63%, 56%, and 23%, respectively.…”
Section: Plant Growthcontrasting
confidence: 65%
See 3 more Smart Citations
“…The yield of lettuce grown in bioponic solution was only one fifth (21%) of the lettuce yield when grown in the Hoagland solution. This was lower than most other published results for yields of bioponically grown lettuce, relative to mineral nutrient solution grown lettuce as reported by Gartman et al [22], Williams and Nelsons [52], Liedl [10], and Atkins and Nichols [55], who obtained 72%, 63%, 56%, and 23%, respectively.…”
Section: Plant Growthcontrasting
confidence: 65%
“…This may have additionally reduced plant growth and could be an explanation for the equally reduced plant growth in the spiked bioponic solution, despite a good NH 4 + :NO 3 − ratio. Increasing the nutrient concentration in the bioponic solution in order to increase yield, as proposed by Gartman et al ( 2023) [22], can, therefore, not be applied to the present study. A more promising approach could be diluting the solution or reducing the number of microorganisms by suitable measures.…”
Section: Plant Growthmentioning
confidence: 93%
See 2 more Smart Citations
“…Studies carried out by (MunungaKatebe et al 2023) showed that the level of contamination, pollution and enrichment of each market garden was not the same, as the majority of gardens were contaminated. We therefore recommend that urban market gardens in Lubumbashi with extremely high levels of contamination, as well as those with exceptionally high levels of pollution, use soilless production techniques such as conventional hydroponics or bioponics to guarantee the quality of the vegetables produced in their gardens to safeguard human health(Dhawi 2023;Gartmann et al 2023;Magwaza et al 2020;Mai et al 2023). The Congolese government must ensure that planning for urban agriculture in the country takes into account the implications of pollution and high levels of contamination on the potential risk posed by market gardens.…”
mentioning
confidence: 99%